The Impact of Personalized Office Spaces on Faculty Productivity, Performance, and Satisfaction in Universities’ Educational Facilities: Case Study of Al Yamamah University, Riyadh, KSA - Dalia Abdelfattah (Buildings, 2025)
Educational facilities are the physical environment that supports the academic process for a better education. The quality of offices as workspaces is crucial in creating a supportive environment to enhance the staff and students’ experience. This paper aims to study the concept of space personalization and its impact on faculty members’ productivity, performance, and satisfaction in universities’ educational facilities. To achieve this aim, the research applied the qualitative research method of semi-structured interviews to gather comprehensive data about user experience. Approaching 39 faculty members within Al Yamamah University across three departments within the College of Engineering (Architecture, Industrial, and Computer). Data were analyzed using thematic analysis for qualitative insights, focusing on environmental aspects (such as: natural lighting, ventilation, noise control, etc.), psychological factors (such as: privacy, aesthetic appeal, etc.), and architectural settings (such as: area, space layout, materials, etc.). The research proposes a methodological framework for design considerations for office spaces in universities, fostering more flexible and personalized designs for enhancing sense of ownership and well-being. Findings indicate that personalized office spaces significantly enhance faculty satisfaction and productivity. Qualitative data highlighted that a lack of privacy in standardized offices adds stress and an overwhelming environment. These findings suggest that universities should consider flexible office designs to optimize academic work environments.